New strategies to address world food security and elimination of malnutrition: future role of coarse cereals in human health - Zou, Xin; Zhang, Jieyu; Cheng, Ting; Guo, Yangyang; Zhang, Li; Han, Xiao; Liu, Changying; Wan, Yan; Ye, Xueling; Cao, Xiaoning; Song, Chao; Zhao, Gang; et al. (Frontiers in Plant Science, 2023)
As we face increasing challenges of world food security and malnutrition, coarse cereals are coming into favor as an important supplement to human staple foods due to their high nutritional value. In addition, their functional components, such as flavonoids and polyphenols, make them an important food source for healthy diets. However, we lack a systematic understanding of the importance of coarse cereals for world food security and nutritional goals. This review summarizes the worldwide cultivation and distribution of coarse cereals, indicating that the global area for coarse cereal cultivation is steadily increasing. This paper also focuses on the special adaptive mechanisms of coarse cereals to drought and discusses the strategies to improve coarse cereal crop yields from the perspective of agricultural production systems. The future possibilities, challenges, and opportunities for coarse cereal production are summarized in the face of food security challenges, and new ideas for world coarse cereal production are suggested.